Clinical judgement and decision-making for nursing students - Standing, Mooi (London SAGE, 2014)
Clinical decision-making is an indispensable facet of professional nursing care. In order to become a registered nurse it is essential that the student develops sound decision-making skills in order to deal with the challenges ahead. This book enables pre-registration nursing students to understand, develop and apply these skills in order to practise safely and effectively. The structure of the book helps students to progress in effective decision-making right from the first to the final year of their programme. The book links theory to realistic experiences and clinical scenarios to show student nurses how to use these skills in practice. This text provides practical ways designed to help student nurses reach sound and safe decisions. It uses active learning features and activities that promote the use of evidence, critical enquiry, reflection and patient-centred care. --
Machine generated contents note: 1. What is clinical judgement and decision-making in nursing? -- 2. Collaborative clinical decision-making -- 3. Using observation to inform decisions -- 4. Systematic clinical decision-making -- 5. Standardised clinical decision-making -- 6. Prioritising decisions in delivering care -- 7. Experience and intuition in decision-making -- 8. Reflective judgement and decision-making -- 9. Ethical sensitivity in decision-making -- 10. Accountability for nursing decisions -- 11. Confidence in clinical decision-making -- 12. Decision-making `PERSON' evaluation tool.
Keywords: Nursing; Clinical medicine; Clinical medicine; Nursing